Perioperative Management of a Post-Cesarean Patient with Severe Preeclampsia, Obstructive Ileus, Sepsis, Acute Kidney Injury, and Decreased Consciousness: A Case Report - Novara, Tendi; Cahyono, Iwan Dwi; Yuniar, Maulana Rizqi (Journal of Anaesthesia and Pain, 2026)
Background: Postoperative ileus following cesarean section is a rare but potentially life-threatening complication in obstetric patients, with an estimated global incidence of 0.1–0.3% and approximately 0.2–0.5% in Indonesia. This condition is primarily caused by reduced bowel motility after surgery and may be precipitated by intra-abdominal manipulation, hemorrhage, electrolyte imbalance, anesthetic effects, or systemic inflammation. In patients with severe preeclampsia, the risk of ileus is further increased due to impaired tissue perfusion, endothelial dysfunction, and postoperative bleeding, which may accelerate progression to multi-organ dysfunction. This case report aims to describe the clinical course, diagnostic challenges, and multidisciplinary management of postoperative ileus complicated by intra-abdominal bleeding, sepsis, and acute kidney injury following cesarean section in a patient with severe preeclampsia. Case: We report a 45-year-old woman (body weight 75 kg, height 155 cm, body mass index 31.2 kg/m²) who developed progressive abdominal distension, decreased level of consciousness, and acute kidney injury one day after undergoing cesarean section for severe preeclampsia. Clinical and radiological evaluations suggested obstructive ileus with suspected intra-abdominal bleeding, accompanied by sepsis and severe metabolic acidosis. Management included mechanical ventilation, blood transfusion, metabolic correction, and emergent hemodialysis under controlled sedation.Conclusion: This case illustrates a continuum of pregnancy-related complications beginning with severe preeclampsia and progressing to postoperative ileus and multi-organ dysfunction. Early recognition and prompt, integrated multidisciplinary perioperative management are essential to reduce morbidity and improve clinical outcomes.